Glycolipid-bound sialic acid in serum: increased levels in mice and humans bearing mammary carcinomas. - Kloppel, T M (1977)
In mice bearing transplantable mammary carcinomas, serum levels of sialic acid-containing glycolipids were elevated 2.5-fold in pooled serum samples from which gangliosides were purified by column chromatography. A method is also described by which ganglioside content was estimated on as little as 1.0 ml of whole blood to permit studies with individual tumor-bearing mice and age- and litter-matched controls. Using this method, we observed similar elevations in ganglioside levels that were independent of age and sex of the animal and appeared in advance of palpable tumors. Following excision of the tumors, the glycolipid sialic acid values dropped below control levels and remained there. Serum sialic acid of the glycolipid fraction was elevated nearly 2-fold in human carcinoma patients and appeared to decline after surgery.